O cultivo do cipó Banisteriopsis caapi e da árvore Psychotria viridis e sua relação com o manejo e a conservação dos recursos florestais e ambientais - Fernandes Neto, Frederico (2023)
The Brazilian Cerrado, the second largest biome in Brazil, stands out as the most diverse savanna in the world and is considered a global biodiversity hotspot. However, in recent decades, this biome has been significantly impacted by land use changes, mainly due to human transformation actions. In this context, members of the Beneficent Spiritist Center União do Vegetal (CEBUDV), a religious organization based on spiritualistic principles, attach great value to nature and use the Hoasca tea as a sacrament in their religious rituals and traditional ceremonies. The sacred plants used are the vine Banisteriopsis caapi and the tree Psychotria viridis, widely recognized and employed by indigenous communities and religious centers. In this sense, UDV is dedicated not only to the responsible use of these sacred plants but also to the valorization of biodiversity and nature conservation. This research aimed to understand how the management of these plants could contribute to biodiversity conservation and the recovery of a degraded area within the UDV's Nucleus (Núcleo Arvoredo) in the 13th region of Cuiabá, Mato Grosso. The first part presents a spatiotemporal analysis of the dynamics of the conserved area within the institution's jurisdiction, along with a phytosociological analysis of forest composition, structure, and diversity. The research results indicated that the cultivation of these plants can be an effective strategy for the conservation of forest and environmental resources, showing a recovery of savanna formation within the area of interest, contrasting with the landscape matrix in the surroundings. A total of 2100 individuals belonging to 35 species were found. The most representative species were Machaerium hirtum, Astronium fraxinifolium, Cordia trichotoma, Astronium urundeuva, and Magonia pubescens, according to the importance value index. The vegetation presents suitable conditions for the conservation and structure of a Cerradão formation area within the regenerating natural process of the Cerrado biome. The second part focuses on an ethnobotanical study with an environmental perspective, aiming to recognize and understand the plant-nature association for the conservation and recovery of degraded areas. Semi-structured interviews were conducted with active members of the religious community of União do Vegetal. The participating members consider themselves key actors in nature conservation and the valorization of biological and cultural diversity. Furthermore, the interviews revealed that the cultivation of these plants can be carried out in agroforestry systems and contribute to conservation and recovery through plant management and use practices, within a framework of ecological self-sustainability, conceiving the sacred in nature itself and as a source of connection to the divine. The research results demonstrate that management based on the perspectives of the União do Vegetal community can significantly contribute to the conservation of natural resources, not only within the institution but also in society as a whole.